PERAN MEDIA PEMBELAJARAN KOMIK DIGITAL UNTUK MENUMBUHKAN MINAT BACA SISWA DI SEKOLAH DASAR - Aditya Rizki Willya; Annisa Luthfiyyah; Putriani Chrismes Simbolon; Arita Marini (Bajang Institute, 2023)
Abstract: One of the abilities that must be mastered by students is the ability to read. A lack of interest in reading can negatively affect students and others. Efforts to increase reading interest are a challenge for teachers. Basically students are less interested in reading because the media that students read is only printed books that are full of writing. An elementary school student needs more interesting media to increase his interest in reading. The existence of interesting pictures and the selection of writing fonts in books makes students interested in reading. Teachers are required to be more creative in making student reading media such as making digital comic learning media that makes reading look different from books in general. This study examines more deeply the role of digital comic learning media in making students interested and enthusiastic about reading. This type of research is a qualitative literature method. Library materials are used as the main source of information. Keywords: Digital Comics, Interest in Reading